Amoebapores, archaic effector peptides of protozoan origin, are discharged into phagosomes and kill bacteria by permeabilizing their membranes - Jörg Andrä and Rosa Herbst and Matthias Leippe (Developmental & comparative immunology : ontogeny, phylogeny, aging ; the official journal of the International Society of Developmental and Comparative Immunology, 2003)
Antimicrobial peptides are widespread in animal species and their function as defensive molecules may even have appeared before the evolution of metazoa. The amoeboid protozoon Entamoeba histolytica discharge membrane-permeabilizing polypeptides named amoebapores into the phagosome in which engulfed bacteria are situated as evidenced here by confocal laser microscopy and electron microscopy using specific antibodies. We demonstrate that the purified three isoforms of the amoebic polypeptides exhibit complementary antibacterial activities in vitro. The potency of amoebapores were compared with that of antimicrobial peptides of phylogenetically widespread species by monitoring in parallel their activities against representatives of gram-positive and gram-negative bacteria and liposomes in various assays, and differences in the mechanism of membrane permeabilization became apparent. Northern blot analysis revealed that expression of genes coding for amoebapores and amoebic lysozymes is not dramatically changed upon co-culture of amoebae with bacteria indicating that the antimicrobial arsenal is rather constitutively expressed than induced in these primitive phagocytes.
Keywords: Antimicrobial peptides; Amphipathic α-helices; Cytolytic; Amoebapores; Entamoeba histolytica; Phagolysosome; Pore formation; Protozoa